Tinjauan Maqasid Syariah Terhadap Tes Kesehatan Pranikah (Analisis Kebijakan KUA Kecamatan Baiturrahman Banda Aceh) - Shifa, Asyi; Khairani; Boihaqi bin Adnan (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2026)
This study aims to analyze the implementation of the premarital health screening policyas an administrative requirement at the Baiturrahman District Religious Affairs Office(KUA), Banda Aceh City, and evaluate its relevance from a maqāṣid syarī‘ahperspective. Using Islamic legal research methods with a normative-empiricalapproach, this study examines the applicable regulations and correlates them with fieldrealities through key informant interviews. The results reveal that premarital healthscreening is integrated into the Marriage Guidance for Prospective Brides and Grooms(Bimwin Catin) program to educate and protect the health of prospective couples.Administratively, the screening is mandatory as a supplement to marriage documents,but does not preclude marriage for candidates with special health conditions. Itsimplementation is supported by cross-sectoral synergy between the Ministry ofReligious Affairs, health agencies, and the National Population and Family PlanningAgency (BKKBN). From the perspective of maqāṣid syarī‘ah, this policy is congruentwith ḥifẓ al-nafs (protection of life), ḥifẓ al-nasl (protection of offspring), ḥifẓ al-‘aql(protection of reason), and ḥifẓ al-māl (protection of property). Thus, this policy goesbeyond the administrative dimension, fulfilling broad benefits for building healthy,harmonious, and quality families.